Listeria Necrotizing Cellulitis: A Case Report - Abi Rached, Emilio; Maamari, Julian; Al Kotob, Abdulrahman; Mokhbat, Jacques (International Journal of Clinical Research, 2022)
Background: L. monocytogenes typically affects pregnant women, neonates, or immunocompromised individuals, with a wide clinical spectrum that includes Central Nervous System (CNS) infections, endocarditis, and very rarely, localized infections such as necrotizing fasciitis . Although L. monocytogenes is the main pathogenic species, there are a total of 21 described species including L. grayi. L. grayi is not a well recognized human pathogen, despite a few case reports of infection in organ transplant patients. Listeria-associated soft tissue infections are exceedingly rare and are typically seen in immunocompromised individuals, with the usual culprit being Listeria monocytogenes. Case Report: We report the case of A 33-year-old previously healthy male, presented to the Emergency Department (ED) with left leg swelling, erythema, and fever. After multiple courses of treatment, we were able to isolate the L.grayi from the intraoperative specimen, confirmed the diagnosis of L.grayi associated cellulitis in a healthy young non-immunocompromised patient. Conclusion: This is to the best of our knowledge the first case of Listeria Grayi associated soft tissue infection in a previously healthy young man 3 months after recovery from COVID-19 infection.